EFFECT OF SCOURING AND BLEACHING TREATMENT ON KNITTED COTTON FABRICS FOR ECONOMIC STUDY - Morshed, Monjur; Azim, Abu Yousuf Mohammad Anwarul; Mukthy, Azmary Akter; Hoque, S. M. Azizul (European Scientific Journal, ESJ, 2014)
Cotton is the leading fibre in Textile Industry. Cotton is still the "King" of fibers because most of the world’s apparel is made of Cotton. Apart from its fairly good strength, it is considered to provide comfort due to good moisture absorption and wicking properties. It is estimated that approx. 20 million tons of Cotton is processed worldwide yearly. Unlike man made cellulosic fibers such as Rayon and Lyocell, Cotton must be properly prepared for Dyeing, printing and finishing. To prepare the cotton fabric ready for Dyeing, printing and finishing scouring & bleaching is the fundamental step. Scouring of cotton textiles is an essential treatment in textile wet processing in order to obtain a sufficiently hydrophilic fabric. During scouring, waxes and other hydrophobic materials are removed from the cotton fibers. cotton fibres are off-white in color due to having colour bodies with it and the process of destruction these colour bodies from fibres is known as bleaching. The problems involved in normal scouring & bleaching using H2O2 is requirement of higher amount of alkali that will result higher cost in Effluent Treatment Plant to remove the alkalinity, use of wetting agent, sequestering agent, detergent & stabilizer and also require acetic acid to neutral the fabric. The aim of our work is to reduce the amount of alkali that is used in scouring , no use of acetic acid after scouring for neutralization and use of single chemical in place of that is cost effective. To fulfill our aim we use Imerol Blue Liquid in place of wetting agent, sequestering agent, detergent & stabilizer that is supplied by Clairiant and compare the Imerol Blue process with classical scouring & bleaching process using stabilizer.